(untitled) (Iraqi Journal of Civil Engineering, 2017)
Chlorine contact tank in water and waste water treatment plant suffer from a lack of efficiency disinfected treated water, which discharge to the rivers and they need a large amount of chlorine for the purpose of disinfection as a result of the presence of dead zones in the basins of chlorine as well as the need to contact a long more than exact standard specifications for the tanks disinfection time. This study deal with optimal performance basin mixing chlorine, which is located at the beginning of Chlorine contact tank of waste water treatment plant in the city of Nasiriyah in Dhi Qar, which is located south of the province of Iraq. In this paper, the use of computational fluid dynamic model in the numerical analysis for the purpose of finding the optimum performance of the chlorine mixing tank with the help of the program FLUENT 6.3.26 and program GAMBIT 2.3.16. Also in this study was used User Defined Function for the purpose of improvements of mixing chlorine. Where the results of the study showed that the ideal rotational speed of the mixer is 140 rpm as well as the results showed Numerical Model that can reduce chlorine dose to 5 mgliter, which is the optimum concentration of chlorine to be supplied for wastewater disinfect and is identical to the Iraqi specifications water sanitation, which discharge to the Euphrates River. In this study the best contact time of chlorine which give the best performance for mixing was 20 seconds.